PENGARUH PROMOSI INFLUENCER DI MEDIA SOSIAL TERHADAP AKTIVITAS BELANJA ONLINE PELAJAR SMA DI KOTA BATAM - Putri Nabila; Yesi " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Social media has started to become a trend since the emergence of web 2.0. The users of Twitter, Instagram, Facebook, Bloggers and Vloggers are now more numerous and rampant (Rosaliza et al., 2022). The birth of social media such as Twitter, Instagram and Facebook has also created a new trend in the world of digital marketing through influencers. Influencers are believed to be capable of developing marketing techniques for a product through their personal social media accounts, and are believed to be able to attract buying interest from consumers. The trend of online shopping today has a lot of enthusiasts, one of which is among high school students, for students nowadays appearance is a way for them to expose themselves, so shopping online is an alternative for students to fulfill the lifestyle that is trending in their environment. , and meet this lifestyle cheaply and affordably so that it fits into student pocket money. (Media et al., 2017). This research was conducted at SMA Negeri 8 Batam City. The purpose of this research is to find out: 1) Online shopping activities of SMA N 8 Batam City students, 2) Promotions carried out by influencers on social media can influence and have an impact on online shopping activities of SMA N 8 Batam students. This study uses a descriptive quantitative method. The technique of collecting data for this research is the distribution of questionnaires and observation. Based on the results of the research, it can be concluded: 1) SMA N 8 Batam students have carried out online shopping activities in the last 6 months as much as 1-3 online shopping transactions and spent more than Rp. 500,000, so that online shopping activities carried out can still be categorized as normal and not excessive, 2) Promotion of a product carried out by Influencers on Social Media based on indicators of Expertise, Trust, Attraction, Similarity, Goods Quality Expectations, Likes & Comments, Number of Followers, Content, and Personal Branding, Batam City 8 Public High School students agree that this is the reason they can be influenced by promotions carried out by influencers on social media so that they are interested in buying the product being promoted. Keywords: Influencer Promotion, Online Shopping, Student